Influence of Particle Orientation on the Performance of Geogrid Reinforced Ballast - Jian-bin Zhao; Jie Li; Xiao-hong Bai; Chen-xi Miao; Jun Zhang (Advances in Materials Science and Engineering)
To explore the initial orientation effect of ballast assembly on the reinforcement performance of the geogrid reinforced ballast, particles with random orientation and five prescribed rotational orientations were developed through particle flow code (PFC3D). The evolution laws of the pullout force and the principal directions of the normal contact force were systematically compared and analyzed. Furthermore, the mechanical responses such as pullout force, distribution of axial force, displacement vectors, force chain, and mesoscopic fabric were discussed. According to the displacement vectors of the ballast particles, the average thickness of the stable shear band is determined. The inherent relationships among the force chain, the rotational angle of the normal contact force, and the mesoscopic fabric parameters are revealed. The results show that the pullout force of specimens with the initial orientation of 45° increases monotonously during the pullout process, and the peak value of pullout force appears at the end of the test. The mesostructural analysis also confirms that the evolution of the principal direction of contact normal force is relatively steady during the pullout process, indicating that the specimen with 45° orientation possesses higher systematic stability and ductility. Moreover, the optimum interval from 56.68° to 57.30° is observed to remain in a self-adapting state for ballast assembly.